Alibaba Group's Taobao : from intermediary to ecosystem enabler - Williamson, Peter J.; Wang Jingji, Michelle ([London] : SAGE, 2016)
This case explores how Alibaba Group has nurtured the creation of a business ecosystem to underpin the success of its Taobao Marketplace and Tmall.com e-commerce businesses that have come to dominate on-line shopping in China.
Originally Published in: Williamson, P., & Wang Jingji, M. (2014). Alibaba Group's Taobao: From intermediary to ecosystem enabler. Cambridge: University of Cambridge, Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Alibaba (Firm); Creative ability in business -- Case studies; Strategic planning -- Case studies